ELEMENTOS CLIMÁTICOS QUE INTERFEREM NO DESENVOLVIMENTO E PRODUÇÃO FINAL EM CANOLA - Kruger, Cleusa A. M. B.; Medeiros, Sandro L. P. d.; Melo, Elder D.; Valentini, Ana P. F.; Gaviraghi, Fernando; Zambonato, Felipe; Battisti, Gabriel K.; Silveira, Rafaela B. d.; Uhde, Leonir; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo